2006
DOI: 10.1007/s10616-006-9039-y
|View full text |Cite
|
Sign up to set email alerts
|

Related effects of cell adaptation to serum-free conditions on murine EPO production and glycosylation by CHO cells

Abstract: The necessity to perform serum-free cultures to produce recombinant glycoproteins generally requires an adaptation procedure of the cell line to new environmental conditions, which may therefore induce quantitative and qualitative effects on the product, particularly on its glycosylation. In previous studies, desialylation of EPO produced by CHO cells was shown to be dependent on the presence of serum in the medium. In this paper, to discriminate between the effects of the adaptation procedure to serum-free me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 66 publications
1
16
0
6
Order By: Relevance
“…The distribution of rhEPO isoforms is another indicator of protein quality, as the terminal sialylation level directly affects the biological activity in vivo [29]. The IEF patterns obtained after 72, 96, and 120 H of cell culture showed that rhEPO glycosylation was constant during the process, which is in accordance with results obtained earlier [21]. However, changes in the molecular weight and sialylation pattern of rhEPO were observed after 168 H of cell culture, indicating that the protein-free HyQ CDM4CHO medium was suitable only for rhEPO production in the early stages of the process.…”
Section: Characterization Of Produced Rhepo In Protein-free Conditionssupporting
confidence: 89%
See 1 more Smart Citation
“…The distribution of rhEPO isoforms is another indicator of protein quality, as the terminal sialylation level directly affects the biological activity in vivo [29]. The IEF patterns obtained after 72, 96, and 120 H of cell culture showed that rhEPO glycosylation was constant during the process, which is in accordance with results obtained earlier [21]. However, changes in the molecular weight and sialylation pattern of rhEPO were observed after 168 H of cell culture, indicating that the protein-free HyQ CDM4CHO medium was suitable only for rhEPO production in the early stages of the process.…”
Section: Characterization Of Produced Rhepo In Protein-free Conditionssupporting
confidence: 89%
“…The productivity of rhEPO in the serum-free HyQ CCM5CHO medium (292.0 ± 5.7 IU/mL) was comparable to that in the DME medium with 10% FBS and 1% FBS (294.0 ± 6.5 and 260.0 ± 9.0 IU/mL, respectively). A reversible decrease was reported in rhEPO production using a medium without serum, whereas the use of enriched medium with higher protein content resulted in the recovery of rhEPO production [21]. Therefore, a high-protein content media (HyQ CCM5CHO medium in the present study) is required to restore rhEPO productivity compromised by the cell adaptation process.…”
Section: Adaptation Of Rcho Cells To Serum-free Conditions and Rhepo mentioning
confidence: 80%
“…CE has been used to study properties of sorghum proteins [188], the effect of iron restriction on the composition of the outer membrane of Pseudomonas strains [189], the effect of several antifungal agents on the protein composition in Candida albicans [190], factors affecting soluble-protein expression [191], effect of different hydrolysates of whey proteins on hepatic glutathione content in mice [192], endogenous serine/threonine Akt phosphorylation [193], dynamic unfolding of regulatory subunit of cAMP-dependent protein kinase [194], glycosylation of recombinant human erythropoietin [195], the effect of heat treatment on properties of Lupinis albus proteins [196], cell adaptation to serum-free conditions on murine erythropoietin production [197], apoptotic pathway in higher eukaryotes [198], nonenzymatic glycosylation of human IgG and HSA with glucosamine and glyceraldehyde [199], thiol distribution in low-density lipoprotein apoprotein [200], structural changes in superoxide dismutase [201], posttranslational modifications of collagen [202,203], proteinprotein interactions [204], aptamers recognizing ricin toxin [205], effect of substrates on enzymatic activity of cellulases from Penicillium brasilianum [206], new enzymatic activities [207], and O-glycosylation of proteins [208].…”
Section: Studying Behavior Of Proteinsmentioning
confidence: 99%
“…Because different cell lines have different requirements and vary considerably from one cell line to another, design of a single serum-free formulation to act as a serum substitute suitable for the growth of all cell line is impossible. Combinations of standard basal media may be tested for best result in terms of good cell number and productivity at minimal serum level [6,7]. In some cases, metabolic analysis may help in media design [8].…”
Section: Introductionmentioning
confidence: 99%